2010
DOI: 10.1111/j.1365-2702.2010.03468.x
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of Turkish version of the Individualised Care Scale

Abstract: The information obtained by the Individualised Care Scale will help nurses to identify areas where developmental work could be undertaken to provide individualised care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 18 publications
4
37
1
3
Order By: Relevance
“…), and Acaroglu and co‐workers adapted the scale to the Turkish population in 2011 (Acaroglu et al . , Acaroglu & Sendir ). The ICS comprises two sections of 17 items each.…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…), and Acaroglu and co‐workers adapted the scale to the Turkish population in 2011 (Acaroglu et al . , Acaroglu & Sendir ). The ICS comprises two sections of 17 items each.…”
Section: Methodsmentioning
confidence: 96%
“…The ICS is a five-item Likert type of scale developed in 2000 by Suhonen et al to make an evaluation of individualised care from the perspective of the patient (Suhonen et al 2000a). The same authors revised the scale in 2005 and reduced the number of items (Suhonen et al 2005a), and Acaroglu and co-workers adapted the scale to the Turkish population in 2011 (Acaroglu et al 2011, Acaroglu & Sendir 2012. The ICS comprises two sections of 17 items each.…”
Section: Individualised Care Scalementioning
confidence: 99%
See 1 more Smart Citation
“…Of these 12 articles, seven describe the Individualized Care Scale (ICS) in its original version, its modification or translations (Suhonen, Välimäki and Katajisto ,b; Suhonen, Leino‐Kilpi and Välimäki ; Acaroglu et al. ; Petroz et al. ; Suhonen et al.…”
Section: Resultsmentioning
confidence: 99%
“…Convergent validity of the ICS has been demonstrated Schmidt 2001). Since its development, many studies have also reported reliability and validity evidence of the scale internationally (Berg et al 2007, Kalafati et al 2007, Land & Suhonen 2009, Acaroglu et al 2011, Petroz et al 2011.…”
Section: The Ics -Patient Versionmentioning
confidence: 99%